Pemberdayaan Masyarakat Melalui Pelatihan Pengelolaan Sampah Menjadi Pupuk Organik Bagi Masyarakat Petani di Kelurahan Sabaru, Kecamatan Sabangau, Kota Palangka Raya - Darlan, Saiffullah; Wahidin; Linggua Sanjaya Usop; Daryana; Palentina (Jurnal Pengabdian Kampus, 2024)
This community service aims to teach dragon fruit farmer groups about how to utilize household waste to make liquid organic fertilizer and how to understand how to do it. Organic waste can be controlled and utilized to make organic fertilizer, which will cut production costs as fertilizer prices continue to increase, affecting farmers' income. The transfer of science and technology in the form of efficient and effective organic fertilizer training should always be included in the development of farmers' skills. The targets of this activity are farmers in Sabaru Village, Sabangau District, Palangka Raya City. These farmers are expected to be more creative and innovative in solving the problem of fertilizer prices and managing waste properly. One of them is by making liquid organic fertilizer made from household waste. It is hoped that this liquid organic fertilizer can increase the income of farmers, as well as how farmers can utilize household waste obtained from the surrounding environment. This activity is part of the PKM Postgraduate PLS work program at Palangka Raya University and took place from June to early July 2024. The techniques used in this activity were lectures, discussions, and questions and answers, as well as direct practice in making liquid fertilizer using household waste as natural ingredients and utilizing EM4 (Effective Microorganisms) bioactivator. The results of this activity showed a level of success, with evidence of increased understanding and proficiency in using EM4 bioactivator. It can be seen through the ability practiced by farmers in treating EM4 bioactivator proficiently, from not knowing to understanding and being able to make natural liquid fertilizer using EM4 bioactivator and utilizing household waste.